Eruption and Interplanetary Evolution of a Stealthy Streamer-Blowout CME Observed by PSP at ∼0.5 AU - Pal, Sanchita; Lynch, Benjamin J.; Good, Simon W.; Palmerio, Erika; Asvestari, Eleanna; Pomoell, Jens; Stevens, Michael L.; Kilpua, Emilia K. J. (Frontiers in Astronomy and Space Sciences, 2022)
Streamer-blowout coronal mass ejections (SBO-CMEs) are the dominant CME population during solar minimum. Although they are typically slow and lack clear low-coronal signatures, they can cause geomagnetic storms. With the aid of extrapolated coronal fields and remote observations of the off-limb low corona, we study the initiation of an SBO-CME preceded by consecutive CME eruptions consistent with a multi-stage sympathetic breakout scenario. From inner-heliospheric Parker Solar Probe (PSP) observations, it is evident that the SBO-CME is interacting with the heliospheric magnetic field and plasma sheet structures draped about the CME flux rope. We estimate that $18 \, ± \, 11%$ of the CME's azimuthal magnetic flux has been eroded through magnetic reconnection and that this erosion began after a heliospheric distance of ${\sim}0.35$ AU from the Sun was reached. This observational study has important implications for understanding the initiation of SBO-CMEs and their interaction with the heliospheric surroundings.